Analisis Terpaan Iklan Humor Joe Taslim x Fadil Jaidi pada Platform Youtube Terhadap Brand Awareness Shampo Head & Shoulder di Kota Denpasar - Pratiwi, Intan Nathasa; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium; Vol 5 No 1 (2024): Jurnal Ilmu Komunikasi Vol 5 No 1 Tahun 2024, 2024)
The use of humor is very effective in getting people to pay attention to advertisements and creating awareness. Humor is one of the accessories that make advertising more interesting. This was done in the Joe Taslim x Fadil Jaidi Head & Shoulders advertisement. The purpose of this study was to find out whether exposure to Joe Taslim x Fadil Jaidi humor advertisements affected Brand Awareness of Head & Shoulder shampoo. This study used a quantitative explanatory research method using the S-O-R (Stimulus-Organism-Response) theory. Respondent data was obtained from 130 respondents aged 9-24 years who live in Denpasar City. The findings from this study indicated that there was an influence of exposure to the humorous advertising of Joe Taslim x Fadil Jaidi on Brand Awareness of Head & Shoulder shampoo in Denpasar City which was at a moderate level with a positive value of 0.527 with an r square of 27.8%